Histological Investigation of the Cleaning Effectiveness of Different Biomechanic Processes of Isthmus in Lower Molars - Aydın, Rabia N.; Gençoğlu, Nimet (European Journal of Dentistry, 2022)
Objectives This study aimed to evaluate the efficacy of different instruments (Hyflex, ROTATE, and hand files) and irrigation methods (EndoUltra, EndoActivator, and side-perforated syringe) in the mesial root canal of a mandibular first molar with isthmuses.Materials and Methods Sixty-three mandibular molar teeth with isthmus were selected using cone beam computed tomography (CBCT) images. The root canals were instrumented with Hyflex, ROTATE, or hand files (21 of each) and three of each as control group and the specimens were embedded in silicone blocks. Final irrigation was performed with the perforated syringe or ultrasonic (EndoUltra) or sonic irrigation (EndoActivator). All canals were irrigated using 5.25% NaOCl solution (15 mL). Then, the roots were stained with hematoxylin–eosin, and specimens were sliced for histologic evaluation. The isthmus regions (2.7, 3, 4.7, and 5 mm from the apex) were analyzed, and the percentage of debris was calculated.Statistical Analysis All data were statistically analyzed using one-way analysis of variance and Tukey's tests.Results Both Hyflex and ROTATE groups showed less debris compared with the hand instrument group (P < 0.05). When irrigation methods were compared, EndoUltra showed the least, followed by EndoActivator and perforated needle irrigation having the maximum debris (p < 0.05). When sections were compared, the maximum debris was found in the apical section and the least in the coronal section (p < 0.05).Conclusion Although none of the methods cleaned the isthmus completely, nickel–titanium (NiTi) systems and ultrasonic and sonic systems removed more debris than the side-perforated needle syringe irrigation.
Keywords: debris; isthmus; sonic irrigation; ultrasonic irrigation